UPAYA INDONESIA MENGGUNAKAN ANGKLUNG SEBAGAI MEDIA DIPLOMASI BUDAYA DI AMERIKA SERIKAT TAHUN 2014-2019 - Raygina Gunawan, Ni Putu Shania; Suwecawangsa, Adi Putra; Sushanti, Sukma (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 4 (2025): JURNAL DIKSHI, 2025)
To support various government initiatives, particularly those aimed at enhancing Indonesia's standing in the international community, the country of Indonesia employs angklung as a diplomatic tool. Therefore, the writer is interested in researching "Indonesia's efforts to use angklung as a medium of diplomacy in the United States in 2014-2019". This study used a descriptive qualitative research method with secondary data types and sources, using literature techniques to collect data. This study uses country-level analysis and using soft diplomacy and cultural diplomacy to analyze this research. One way to maintain and develop the relationship that has been fostered by Indonesia and the United States is to carry out diplomacy using the angklung. The government, through the Cultural Diplomacy Program, bilateral agreements, and the community, the SAU organization, and the House of Angklung, all made efforts to introduce angklung. Indonesia has a opportunity to examine the advantages of bilateral ties between the two nations thanks to the notion of cultural diplomacy, which highlights the significance of art and culture as a weapon for bettering international relations. By recognizing cultural similarities and contrasts, soft diplomacy that promotes culture strengthens ties between Indonesia and the United States.